Consensus exercise identifying priorities for research in the field of general surgery of childhood in the UK. Issue 2 (28th February 2021) - Hall, N J; Rees, C M; Rhodes, H; Williams, A; Vipond, M; Gordon, A; Evans, D A; Wood, R J; Bytheway, J; Sutcliffe, J; ,
Abstract: Background: The evidence base underlying clinical practice in children's general surgery is poor and high-quality collaborative clinical research is required to address current treatment uncertainties. The aim of this study was, through a consensus process, to identify research priorities for clinical research in this field amongst surgeons who treat children. Methods: Questions were invited in a scoping survey amongst general surgeons and specialist paediatric surgeons. These were refined by the study team and subsequently prioritized in a two-stage modified Delphi process. Results: In the scoping survey, a total of 226 questions covering a broad scope of children's elective and emergency general surgery were submitted by 76 different clinicians. These were refined to 71 research questions for prioritization. A total of 168 clinicians took part in stage one of the prioritization process, and 157 in stage two. A 'top 10' list of priority research questions was generated for both elective and emergency general surgery of childhood. These cover a range of conditions and concepts, including inguinal hernia, undescended testis, appendicitis, abdominal trauma and enhanced recovery pathways. Conclusion: Through consensus amongst surgeons who treat children, 10 priority research questions for each of the elective and emergency fields have been identified. These should provide a basis for the development of high-quality multicentre research projects to address these questions, and ultimately improve outcomes for children requiring surgical care.